2010
DOI: 10.1029/2007jc004503
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational circulation and its response to the variation in river discharge in the Seto Inland Sea, Japan

Abstract: [1] In this study gravitational circulation and its response to the variation in river discharge have been investigated in the Seto Inland Sea, Japan. Monthly hydrographic surveys have been conducted from 2002 to 2006 in Hiuchi-Nada, a basin located between two straits. Horizontal salinity gradients along the channel varied as the 9/10 power of the river discharge into one end of the basin. Significant volume fluxes which were proportional to the horizontal salinity gradients were found. The relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…8g and h) is in general agreement with the results from a previous numerical simulation that incorporated realistic bottom topography and the observed density structure in Hiuchi Nada [12]. In the numerical simulation with realistic topography [12], the straits and associated density field were not located on opposite sides of the model domain at the same latitude (as in our simulation), which resulted in asymmetric residual flows that induced a significant flux of strait outflow into the upper layer of the basin. Although the large differences in topography between real sea and model domain, the facts that the residual currents from the strait to the basin were obtained in the numerical simulation, suggested that tides and the horizontal density gradients between the strait and the basin play essential role in driving those residual currents.…”
Section: Driving Force Of the Exchange Flow In A Strait-basin Systemsupporting
confidence: 90%
See 2 more Smart Citations
“…8g and h) is in general agreement with the results from a previous numerical simulation that incorporated realistic bottom topography and the observed density structure in Hiuchi Nada [12]. In the numerical simulation with realistic topography [12], the straits and associated density field were not located on opposite sides of the model domain at the same latitude (as in our simulation), which resulted in asymmetric residual flows that induced a significant flux of strait outflow into the upper layer of the basin. Although the large differences in topography between real sea and model domain, the facts that the residual currents from the strait to the basin were obtained in the numerical simulation, suggested that tides and the horizontal density gradients between the strait and the basin play essential role in driving those residual currents.…”
Section: Driving Force Of the Exchange Flow In A Strait-basin Systemsupporting
confidence: 90%
“…The horizontal circulation shown in the numerical simulation ( Fig. 8g and h) is in general agreement with the results from a previous numerical simulation that incorporated realistic bottom topography and the observed density structure in Hiuchi Nada [12]. In the numerical simulation with realistic topography [12], the straits and associated density field were not located on opposite sides of the model domain at the same latitude (as in our simulation), which resulted in asymmetric residual flows that induced a significant flux of strait outflow into the upper layer of the basin.…”
Section: Driving Force Of the Exchange Flow In A Strait-basin Systemsupporting
confidence: 89%
See 1 more Smart Citation
“…Net seaward flows develop throughout the lower reaches of those estuaries with the largest annual river pulses. In contrast, the Vietnamese Ba Lat River (van Maren and Hoekstra 2004) and the Japanese Seto Inland Sea (Kobayashi et al 2010) show the opposite behavior, with largest gravitational exchanges occurring with increased river inputs. Development of two-layer gravitational exchange or unidirectional seaward flow in response to river pulses might be diagnosed with the Estuarine Richardson Number R E (Fischer et al 1979):…”
Section: Introductionmentioning
confidence: 77%
“…No substantial reversals in this pattern occurred during the period of data collection at Cocodrie and thus, mode 2 appears to be gravitationally-driven estuarine exchange flow, and this exchange flow responded strongly to variations in the longitudinal salinity gradient. The dependence of gravitational circulation on the longitudinal density gradient has been described analytically by [2], and numerous observational studies have documented this response, where enhanced density gradients drove stronger gravitational circulation [42] or even reversed it in the case of inverse estuaries where estuarine salinities exceeded those in shelf waters [43][44][45][46][47].…”
Section: Vertical Variation In Subtidal Velocity Dtructure At Cocodriementioning
confidence: 99%